Intravenous administration of human amnion-derived mesenchymal stem cells improves gait and sensory function in mouse models of spinal cord injury - Tsuji, Shoichiro; Kuramoto, Yoji; Rajbhandari, Saujanya; Takeda, Yuki; Yamahara, Kenichi; Yoshimura, Shinichi (Frontiers in Cell and Developmental Biology, 2024)
Spinal cord injury (SCI) remains a significant social and economic loss. However, effective treatments have still not been established. Therefore, we investigated the therapeutic potential of intravenously administered human amniotic mesenchymal stem cells (hAMSC) in SCI models. Three-dimensional behavioral analysis revealed significant improvements in motor function during the chronic phase and substantial improvement in sensory threshold in paw withdrawal reflex with a von Frey filament. In our experiments, hAMSC treatment significantly suppressed Iba-1-positive cells by immunostaining and significantly suppressed TNFα and increased BDNF by reverse transcription polymerase chain reaction at the site of SCI. For inflammatory reactions outside the site of spinal cord injury, i.e. systemically, flow cytometry of bone marrow cells showed that hAMSC treatment suppressed M-MDSCs and Ly6C-positive cells (so-called M1 inflammatory macrophages). Furthermore, serum NO levels were also suppressed by hAMSC treatment. Taken together, significant improvements are presumed to result from the suppression of inflammation locally and systemically, as well as neuroprotective effects at the SCI site. Our findings suggest promising clinical applications in the future.